Progressive Protrusive Tongue Exercise Does Not Alter Aging Effects in Retrusive Tongue Muscles - Glass, Tiffany J.; Figueroa, Joanie E.; Russell, John A.; Krekeler, Brittany N.; Connor, Nadine P. (Frontiers in Physiology, 2021)
Purpose: Exercise-based treatment approaches for dysphagia may improve swallow function in part by inducing adaptive changes to muscles involved in swallowing and deglutition. We have previously shown that both aging and progressive resistance tongue exercise, in a rat model, can induce biological changes in the genioglossus (GG); a muscle that elevates and protrudes the tongue. However, the impacts of progressive resistance tongue exercise on the retrusive muscles (styloglossus, SG; hyoglossus, HG) of the tongue are unknown. The purpose of this study was to examine the impact of a progressive resistance tongue exercise regimen on the retrusive tongue musculature in the context of aging. Given that aging alters retrusive tongue muscles to more slowly-contracting fiber types, we hypothesized that these biological changes may be mitigated by tongue exercise. Methods: Hyoglossus (HG) and styloglossus (SG) muscles of male Fischer 344/Brown Norway rats were assayed in age groups of young (9 months old, n=24), middle-aged (24 months old, n=23), and old (32 months old, n=26), after receiving an 8-week period of either progressive resistance protrusive tongue exercise, or sham exercise conditions. Following exercise, HG and SG tongue muscle contractile properties were assessed in-vivo. HG and SG muscles were then isolated and assayed to determine myosin heavy chain isoform (MyHC) composition. Results: Both retrusive tongue muscle contractile properties and MyHC profiles of the HG and SG muscles were significantly impacted by age, but were not significantly impacted by tongue exercise. Old rats had significantly longer retrusive tongue contraction times and longer decay times than young rats. Additionally, HG and SG muscles showed significant MyHC profile changes with age, in that old groups had slower MyHC profiles as compared to young groups. However, the exercise condition did not induce significant effects in any of the biological outcome measures. Conclusions: In a rat model of protrusive tongue exercise, aging induced significant changes in retrusive tongue muscles, and these age-induced changes were unaffected by the tongue exercise regimen. Collectively, results are compatible with the interpretation that protrusive tongue exercise does not induce changes to retrusive tongue muscle function.